Impact of systemic health on treatment outcomes in endodontics - Segura-Egea, Juan J.; Cabanillas-Balsera, Daniel; Martín-González, Jenifer; Cintra, Luciano T. A. [UNESP] (Wiley, 2022)
Background: The healing of periapical lesions after root canal treatment (RCT) is not the result of the curative action of the treatment. The process of healing begins with inflammation, and is resolved by the clearance of the immunogen that induces the immune response. Then, the periapical tissue itself carries out the healing of the periapical lesion, by repair or by a combination of repair and regeneration, depending on the host's reparative response working properly. The ultimate objective of RCT is to achieve wound healing by removing the source of bacterial antigens and toxins, allowing chronic inflammatory tissue to become reparative tissue. Some systemic conditions increase the susceptibility of the host to infection or impair the tissue reparative response, maintaining the inflammatory process and periapical bone resorption after RCT. This can cause the failure of RCT and even the need for extraction of the affected tooth. Objective: To analyse the scientific literature on the possible influence of systemic conditions on the treatment outcomes in endodontics, as well as to discuss the biological mechanisms that may be involved. Methods: The search was carried out in PubMed, SCOPUS and EMBASE. The inclusion criteria established were original scientific articles reporting data about some systemic condition in relation to treatment outcomes in endodontics, including clinical studies and studies carried out in animal models. Results: Systemic factors (age, nutrition, stress, hormones, smoking habits), and systemic diseases, such as diabetes, cardiovascular diseases, osteoporosis, HIV infection, inflammatory bowel disease, and others, can influence or interfere in the repair of periapical tissues after RCT. Discussion: Some of these systemic diseases can alter bone turnover and fibroblast function, preventing or delaying periapical wound healing. Others can alter the microvasculature, reducing nutrients and oxygen supply to periapical tissues. As a result, these systemic conditions can decrease the success rate of RCT and provoke incomplete wound healing (typically granulomatous tissue formation) in the periapical region. Conclusions: The results of this narrative review show worse success rate of RCT, with higher percentage of postoperative radiolucent periapical lesions and higher proportion of non-retained teeth (RFT), associated with several systemic conditions, such as smoking habits and diabetes.
Keywords: diabetes; endodontic medicine; endodontic treatments; root canal treatment outcome; smoking; systemic diseases; vital pulp therapy